PERSEPSI WARGA BELAJAR TERHADAP KOMPETENSI SOSIAL TUTOR DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) INSAN CENDEKIA KOTA PEKANBARU - Yolanda, Niva; Ayub, Daeng; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Tutor social competence is an ability that tutors must have to communicate and interact effectively with learning citizens, fellow educators, education personnel, parents / guardians of learning residents, and the surrounding community. The purpose of this study was to determine how high the perceptions of learning citizens towards tutors' social competencies and to find out how much the contribution of citizens' perceptions of learning to tutors' social competencies was based on indicators of the variables of perceptions of learning citizens at the Insan Scholar Community Learning Center (PKBM) Pekanbaru City. This research is a quantitative descriptive variable of one variable. The population in this study were 48 people learning package C in Insan Cendekia PKBM. Sampling in this study was carried out using the Simple Random Sampling technique, because the sampling of members of the population was carried out randomly without regard to strata in the population. The instrument in this study was a questionnaire or questionnaire containing 47 statements about tutor's social competence consisting of three indicators. The mean of the indicators communicating and socializing effectively with learning citizens 4.47, then the indicator mean communicating and socializing effectively with fellow educators and education personnel 4.41, and the mean indicators communicating and communicating effectively with parents / guardians of learning citizens and communities around 4.37. With an average Mean indicator of 4.42 and a standard deviation of 0.20, which is relatively high. Based on inferential statistical analysis, it was found that the contribution of perceptions of learning citizens to tutors' social competencies was classified as high with an average value of 65.03% and the remaining 34.97% was influenced by other indicators besides the indicators in this study.Key Words: Perception, Learning Citizens, Social Competence